PENGARUH BAHAN ASAL STEK DAN MEDIA TANAM TERHADAP PERTUMBUHAN NILAM (Pogostemon cablin Benth) - Simatupang, River Wedilen Bona; Aji, Irwan Mahakam Lesmono; Rini, Dwi Sukma (Jurnal Silva Samalas, 2020)
Patchouli plant (Pogostemon cablin Benth.) is one of the essential oil producing plants that is useful in the fields of pharmaceutical, cosmetics and perfume as a mixture or fixation (binding of fragrances). The success rate of patchouli early growth, is largely determined by the cultivation techniques used, one of which includes vegetative cultivation of various selected stem cutting, and planting media. This study aims to determine the effect of material from cuttings and planting media on the growth of patchouli plants. The research was conducted at the Greenhouse of the University of Mataram Forestry Study Program, using a Factorial Completely Randomized Design (FCRD). The first factor is various stem cutting with three levels, namely tip stem cuttings, middle stem cuttings and base stem cuttings and the second factor is planting media with four levels, namely forest soil media, soil:cocopeat (1:1), soil:cocopeat (1:2) and soil:cocopeat (2:1). The results showed that the effect of material from stem significantly affected the percentage of life, number of shoots, number of leaves, shoot length. For the planting media, it had a significant effect on the length of the shoot, shoot diameter, leaf area, dry trimming weight. The interaction effect of various stem cutting and plan media did not have a significant effect on the growth parameters of patchouli. The treatment of material from cuttings in patchouli plants had the best growth effect on the treatment of S2 (middle stem cuttings) and the treatment of planting media had the best growth effect on the M0 (soil media) treatment.